PENGUATAN NILAI-NILAI SUFISME DALAM NYADRAN SEBAGAI KHAZANAH ISLAM NUSANTARA - Ibda, Hamidulloh (JURNAL ISLAM NUSANTARA, 2018)
This article discusses nyadran, Sufism values in it, and the strategy to preserve it. The findings in this article, nyadran is as one of the archipelago Islamic treasures having high Sufism values. Sufism values contained in nyadran are longing, holding back lust, self-examination, repentance, ascestism, wisdom, maintaining purity, courage, and the value of justice. There are several strategy to preserve nyadran in the fourth Industrial Revolution era so that Muslims will not be disruption from their culture. First, the movement to save humanity from the condition of confusion through nyadran. Second, the incorporation of inner aspects and modernity through nyadran. Third, educate the public that nyadran contains Sufism values. Fourth, the development of nyadran through cultural and religious based tours. Fifth, the concept of cultural parties in nyadran. Sixth, community dialogue with preacher, ulema, modin with the aim of discussing understanding, wisdom, and the benefits of nyadran for social life, nature, and aspects of worship to God.